Jacob Böhme and his world - Andersson, Bo, 1955-; Martin, Lucinda, 1965-; Penman, Leigh (Aries Book Series, 2018)
Jacob Böhme (1575-1624) is famous as a shoemaker and spiritual author. His works and thought are frequently studied as a product of his mystical illumination. Jacob Böhme and His World adopts a different perspective. It seeks to demystify Böhme by focusing on aspects of his immediate cultural and social context and the intellectual currents of his time, including Böhme's writing as literature, the social conditions in Görlitz, Böhme's correspondence networks, a contemporary "crisis of piety," Paracelsian and kabbalistic currents, astrology, astronomy and alchemy, and his relationship to other dissenting authors. Relevant facets of reception include Böhme's philosophical standing, his contributions to pre-Pietism, and early English translations of his works.